An Overview of Thematic Evolution of Physical Therapy Research Area From 1951 to 2013 - Moral-Munoz, Jose A.; Arroyo-Morales, Manuel; Herrera-Viedma, Enrique; Cobo, Manuel J. (Frontiers in Research Metrics and Analytics, 2018)
Physical Therapy is a profession which development and conceptual framework have been performed in the XX century. One of the major challenges of Physical Therapy in the XXI century is to identify the intellectual basis of its scientific domain. The aim of the present paper is to analyze the evolution of Physical Therapy research throughout scientific literature published in Web of Science and Scopus databases. In order to perform the analysis, Web of Science and Scopus bibliographic databases were used to download all records. A set of journals with overall topics in Physical Therapy discipline with the largest history in the Journal Citation Report were selected: Physiotherapy, Physical Therapy, and Australian Journal of Physiotherapy/Journal of Physiotherapy. The bibliometric tool SciMAT was employed to perform a science mapping analysis in order to detect and visualize the research themes and their evolution across three periods: 1951-1984, 1985-2000 and 2001-2013. The analysis carried out shows that Physical Therapy research field is mainly divided into nine thematic areas: Middle Aged People, Muscle Function Alterations and Recovery, Health Education, Gait and Biomechanics, Central Nervous System, Heart Rate and Exercise, Diagnosis, Low Back Pain, and Animals. In conclusion, Physical Therapy citations and production are primarily focused on two large thematic areas, diseases that involve middle-aged population and muscle function and its alterations. Results can be used to provide a historical perspective on research conducted in this emerging field and to provide a scientific evidence-based practice model on which future studies can be built.